The Efforts to Resolve the Prolonged South China Sea Conflict According to the perspective of the United Nations Convention on The Law of the Sea (UNCLOS) - Resya Mauludina; Wellinda Rizka Sulistiara; Slamet Muliono Redjosari (Lampung Center for Global Studies (LCGS), 2023)
The power struggle in the South China Sea region has become an important topic of public discussion. Several ASEAN countries, including Indonesia, as well as the influence of the United States and Chinese powers, are strategically competing for maritime trade routes and rich potential resources. This study aims to analyze the geopolitical phenomena in the South China Sea region. Since 2010, when China claimed Indonesia's exclusive economic zone in the northern part of the Natuna Islands, Indonesia has been